(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Anggraeni TDA, Waluyo B, Sugiharto AN, Kuswanto. 2022. Genetic diversity analysis among 123 accessions of castor (Ricinus communisL.) using SSR marker and its association to agronomic traits. Biodiversitas 23: 1211-1221. Castor (Ricinus communis L.) breeding program targets to create dwarf-type plants suitable for mechanical harvesting. Characterization of plantsusing morphological and molecular markers can enhance the successful breeding program. This studyaimed to investigate the diversity of castor accessionsusing Simple Sequence Repeat (SSR) markers and find the SSR markers that are significantly associated with the agronomic traits. The castor germplasm collection consisting of 123 accessions from the islands throughout Indonesia, breeding lines, and introducedaccessions displayed a moderate genetic diversity. The germplasm collection showed high variation in plant height, node length average, number of nodes, 100 seed weight, and oil content. The association analysis using GLM (General Linear Model) and MLM (Mixed Linear Model) could detect six associations between SSR marker alleles and agronomic traits. Among the marker alleles, two marker alleles had an overlap association. RcSSR-12_175 had an association with plant height and flowering day, RcSSR-23_113 had an association with node length average and branch number, and RcSSR-4_125 had an association with seed weight/raceme. This finding could provide information on Indonesia’s castor accession status. The linked-trait SSR markers are useful in marker-assisted selection for breeding high yield dwarf type-castor.